1987
DOI: 10.1002/j.1939-4640.1987.tb00980.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long‐Term: Opiate Antagonist Administration to Pubertal Boys

Abstract: To test further the hypothesis that opiatergic pathways controlling gonadotropin production may be functional during early to mid adolescence, nine pubertal boys with bone ages ranging from 10 to 15 were given the long-acting opiate antagonist, naltrexone, for up to 4 weeks. Urinary gonadotropin measurements were assessed before, during, and after drug administration. In three early to mid-pubertal boys who received naltrexone for 3 to 4 weeks, LRH testing was also performed. No evidence of a stimulatory FSH o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One human study demonstrated a more sensitive luteinizing hormone surge in pubertal boys than prepubertal, sexually immature boys after chronic 1‐month exposure of naltrexone . Another study found no effect on puberty in boys with confirmed bone age 10 to 15 years when given naltrexone for 1 month .…”
Section: Recommendations (Table )mentioning
confidence: 99%
“…One human study demonstrated a more sensitive luteinizing hormone surge in pubertal boys than prepubertal, sexually immature boys after chronic 1‐month exposure of naltrexone . Another study found no effect on puberty in boys with confirmed bone age 10 to 15 years when given naltrexone for 1 month .…”
Section: Recommendations (Table )mentioning
confidence: 99%